Liberdade e Natureza : o problema da finitude e infinitude da vontade na Introdução da Filosofia do Direito de Hegel - RAMALHO, Julia Sebba (2010)
This study is an analysis of the development of the concept of free will in the introduction of Hegel's Philosophy of Law. In this text, Hegel discusses the concept of will in three figures (Gestalt) or three levels (Stufen), which are the natural will, free will and free will in and of itself. The first two figures reveal finitely freedom, while the latter expresses it so infinite. Therefore, the analysis of the development of these levels will focus on the problem of finitude and infinitude of manifestation and realization of freedom in the objective world of the spirit. The problem of this theme, in fact, is that the will, as a moment (Moment) of self-determination of free spirit, by its nature has the presupposition and starting point. Thus, to investigate the issue of freedom of the will in their different ways of expression, is to investigate, first of all, the relationship between freedom and nature, or rather, is to investigate the relationship between self-determination of the will with its contents volitional natural such as desires and inclinations. Therefore, the analysis of this thesis uses the theming of Hegel made in the Philosophy of Subjective Spirit, where the philosopher addresses the relationship between speculative nature and free spirit. The interpretative hypothesis argues that this work is the assertion that the problem of the finitude of freedom does not respect the fact that the will to self-determine content for natural, therefore, in Hegel, we can find a holistic consideration of the relationship between freedom and nature. Therefore, both the finite modes of development of freedom of will, and in its full and infinite mode, wanting to seek satisfaction is determined by content coming from nature, without thereby cease to be free and autonomous. Thus, this paper will seek to show that Hegel's conception of free will is not a purist design, which sought to establish the world's human spirit by exclusion of its relationship with the natural.